Does Shiga Toxin-Producing Escherichia coli and Listeria monocytogenes Contribute Significantly to the Burden of Antimicrobial Resistance in Uruguay? - Mota, María Inés; Vázquez, Sylvia; Cornejo, Cecilia; D'Alessandro, Bruno; Braga, Valeria; Caetano, Ana; Betancor, Laura; Varela, Gustavo (Frontiers in Veterinary Science, 2020)
Shiga toxin-producing Escherichia coli and Listeria monocytogenes are worldwide recognized zoonotic pathogens. Recent reports have emerged about the circulation of antimicrobial resistant STEC and L. monocytogenes isolates. To assess the frequency of antimicrobial resistance and related genes in these pathogens we studied 45 STEC and 50 Listeria monocytogenes isolates locally recovered from different sources. Antimicrobial susceptibility testing was performed by disk-diffusion method and the genomic sequences of 3 selected STEC and from all 50 L. monocytogenes isolates were analyzed for antibiotic resistance genes. Four STEC and 3 L. monocytogenes isolates were phenotypically resistant to at least one of the antibiotics tested. Resistance genes aph(3'')-Ib, aph(3')-Ia, aph(6)-Id, blaTEM-1B, sul2, mef(A) and tet(A) were found in a human STEC ampicillin-resistant isolate. All L. monocytogenes isolates harbored fosX, lin, mdrL, lde fepA and norB. Overall resistance in L. monocytogenes and STEC was low or middle. However, the high load of resistance genes found, even in susceptible isolates, suggests that these pathogens could be contribute to the burden of antimicrobial resistance.